BUSINESS CAPITAL AND LABOR AFFECT TOBACCO FARMERS' INCOME IN KABAR VILLAGE, EAST LOMBOK - Jalil, Muh. Rabbul (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2024)
Tobacco (Nicotiana Tabacum L) is one of the agricultural commodities that has contributed to the economy in Indonesia. Tobacco is a commodity that has important meaning because apart from providing economic benefits, social benefits. The role of tobacco and the tobacco products industry in the socio-economic life of society is state revenue in the form of excise and foreign exchange, providing employment opportunities, as a source of income for farmers, laborers and traders as well as regional income. The aim of this research is, among other things, to determine the effect of business capital and labor on tobacco farming income in Kabar Village, Sakra District, East Lombok Regency. The research method used is quantitative with research data sources from primary and secondary data. Sampling in this research used the Purposive Sampling method, with a sample size of 40 respondents. The data analysis method used simple linear regression to analyze the influence of business capital and labor on farmers' business income. Based on the results of simple linear regression, among others: (1) Business capital has a significant effect on the total business income of tobacco farmers. (2) Meanwhile, labor does not have a significant effect on tobacco farmers' business income.